Analysis Of The Effect Of Social Media Marketing, Social Influence, Facilitating Conditions, Performance Expectancy, And Effort Expectancy Affect Brand Awareness Through Brand Loyalty As An Intervening Variable For Scarlett Whitening Consumers In Kupang City - Trixi soraya haba; Yanuar dananjaya; Hananiel M. Gunawan (Jurnal Ekonomi, 2024)
In today's modern era, the development of the beauty product business is multiplying. People, especially women, are increasingly aware of the importance of cosmetics as a daily necessity, and the demand for someone to look attractive in front of the public is one of the reasons the cosmetics industry is growing well in Indonesia. For women, appearance and beauty are essential because they are supported by popularity, social status, life, and career choices influenced by one's physical attractiveness. Beauty and body care products can meet women's needs for beauty, which is also a means for consumers to explain social self-identity in the eyes of society (Ferrinadewi, 2016). Google collected the data from this study from electronic questionnaires from 105 respondents who had purchased skincare at Scarlett Whitening in Kupang City. This study using SPSS was used to assess the relationship between variables. This study shows that Social Media Marketing, Social Influence and Facilitating Conditions, Performance Expectancy, and Effort Expectancy significantly affect Brand Awareness and Loyalty. This shows that retail businesses, especially sales, should consider these variables to increase sales.